Narrative Construction of Conflict in Koran Kaltim’s Coverage of the Karang Mumus River Normalization Program - Sitti Syahar Inayah; A.Rivai Beta (DAWUH : Islamic Communication Journal, 2026)
This study examined the narrative construction of conflict in Koran Kaltim’s reporting on the Karang Mumus River normalisation program Although news is often presented as objective and factual, the findings showed that news texts also function as narratives, featuring characters, conflict, and causal sequences. Using a qualitative, narrative analysis, this research examined six news articles published between 2022 and 2025. Vladimir Propp’s narrative framework was applied to identify narrative structures, the dramatisation of conflict, and the positioning of social actors within the news. The results indicated that the news was organised as a coherent narrative with a clear linear progression, beginning from the emergence of conflict and leading to its resolution. Conflict was mainly constructed around issues of compensation uncertainty and the demolition process. In addition, the study consistently found a pattern of binary opposition, in which government actors were portrayed as legitimate problem solvers, while affected residents were portrayed as obstacles to policy implementation. This study contributed to the field of narrative journalism by showing that routine news reporting could function as a structured narrative,thereby extending the application of Propp’s theory into news discourse. From an Islamic perspective, the findings also emphasised the ethical importance of fair and balanced representation, particularly in relation to the concept of mazhlum (the oppressed). This highlights the need for more inclusive and socially responsible media narratives